Small RNA-based plant protection against diseases - Bilir, Özlem; Göl, Deniz; Hong, Yiguo; McDowell, John M.; Tör, Mahmut (Frontiers in Plant Science, 2022)
Plant diseases cause significant decreases in yield and quality of crops and consequently pose a very substantial threat to food security. In the continous search for environmentally friendly crop protection, exploitation of RNA interferance machinery is showing promising results. It is well established that small RNAs (sRNAs) including microRNA (miRNA) and small interfering RNA (siRNA) are involved in the regulation of gene expression via both transcriptional and post-transcriptional RNA silencing. sRNAs from host plants can enter into pathogen cells during invasion and silence pathogen genes. This process has been exploited through Host-Induced Gene Silencing (HIGS), in which plant transgenes that produce sRNAs are engineered to silence pest and pathogen genes. Similarly, exogenously applied sRNAs can enter pest and pathogen cells, either directly or via the hosts, and silence target genes. This process has been exploited in Spray-Induced Gene Silencing (SIGS). Here, we focus on the role of sRNAs and review how they have recently been used against various plant pathogens through HIGS or SIGS-based methods and discuss advantages and drawbacks of these approaches.